Pengaruh Nilai-Nilai Islam Terhadap Strategi Pengelolaan Keuangan Generasi Z Di Era Digital - Arfandy Dian Nugraha; Andi Patimbangi; Hartas Hasbi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of Islamic values on the financial management strategies of Generation Z in the digital era. As a generation born in the digital age, Generation Z has unique characteristics in managing finances, often influenced by a consumerist lifestyle and technological advancements. This research employs a qualitative approach with a phenomenological method, focusing on individuals' subjective experiences in understanding financial management based on Islamic values. Data were collected through interviews, observations, and documentation involving Generation Z in Cellu Village, Tanete Riattang Timur District, Bone Regency, South Sulawesi. The findings indicate that Islamic values, such as the principles of justice, the prohibition of usury (riba), transparency, and the importance of zakat, infaq, and sadaqah, play a significant role in shaping Generation Z's financial management strategies. However, challenges such as limited Islamic financial literacy and the temptation of a consumerist lifestyle often hinder effective implementation. Additionally, the digital era presents both opportunities and challenges in financial management, offering easy access to technology and Islamic finance applications. This study is expected to provide new insights into the importance of Islamic financial literacy for Generation Z and encourage the application of Islamic values in effective and beneficial financial management, particularly in the digital era, which is filled with both challenges and opportunities